Efficacy of different surgical approaches in the clinical and survival outcomes of patients with early-stage cervical cancer: protocol of a phase III multicentre randomised controlled trial in China - Chao, Xiaopei (BMJ Open, 2019)
INTRODUCTION: In the last three decades, minimally invasive surgery (MIS) for radical hysterectomy (RH) has become a popular treatment option for early-stage cervical cancer. However, a recently published randomised controlled trial (LACC trial) and an epidemiological study in the USA revealed strong evidence against the survival advantage of MIS for RH. However, the influencing factors of research centres and the learning curves of surgeons in these studies lacked sufficient evaluation. The efficacy of different surgical approaches for early-stage cervical cancer in the clinical and survival outcomes remains to be validated. METHODS AND ANALYSIS: Patients diagnosed with FIGO (2009) stage IA1 (with lymphovascular space invasion), IA2 or IB1 cervical cancer with histological subtype of squamous cell carcinoma, adenocarcinoma or adenosquamous carcinoma will be recruited in this multicentre randomised controlled study. Patients will be randomly assigned to undergo MIS (robot-assisted or laparoscopic RH) or abdominal RH. Within 2 years, 1448 patients in 28 centres in China will be recruited to meet the criteria of a non-inferiority threshold of HR of 1.6 with bilateral nominal α <0.05 and power of 0.8. All surgeries will be performed by the indicated experienced surgeons. At least 100 RH cases in the individual past one decade of practice will be analysed as proof of learning curves. The primary objective of this study is 5-year disease-free survival. The secondary objectives include the overall survival rate, progression-free survival rate, disease-free survival rate, cost-effectiveness and quality of life. ETHICS AND DISSEMINATION: This study has been approved by the Institutional Review Board of Peking Union Medical College Hospital and is filed on record by all other centres. Written informed consent will be obtained from all eligible participants before enrolment. The results will be disseminated through community events, academic conferences, student theses and peer-reviewed journals. TRIAL REGISTRATION NUMBER: NCT03739944.